The Influence of Human Resources and Infrastructure on the Performance of Military Teachers in Special Forces Training Education Centers - I Wayan Laba; Ferikawita Magdalena Sembiring (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2024)
The research, entitled